The logic of scientific discovery - Popper, Karl Raimund, Sir, 1902- (New York : Routledge, 1999)
An English translation of the 1934 text in which German philosopher Karl Popper refutes the opinion that science is fundamentally inductive in nature and proposes a criterion of testability, or falsifiability, for scientific validity.
"First published 1959"--T.p. verso.
Translation of: Logik der Forschung.
Includes bibliographical references and indexes.
Young Adult
Keywords: Science -- Methodology; Science -- Methodology